Encapsulation of Sesbania grandiflora extract in polymeric micelles to enhance its solubility, stability, and antibacterial activity - Pimporn Anantaworasakul (2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Clinical applications of Sesbania grandiflora bark extract (SGE) are limited because of its poor water solubility and stability. SGE was loaded in micelles of Pluronics. In vitro and in vivo antibacterial and toxicity tests were investigated using broth dilution and silkworm model. Aqueous solubility of SGE was improved by these micelles. Activity and toxicity of SGE loaded micelles were dependent on type and concentration of Pluronics. The micelles composed of 1:3 SGE to Pluronic F68 (SGE-PF68-13) showed small size (24.95 ± 0.34 nm), narrow PdI ( < 0.2), high entrapment efficiency (99.63 ± 0.19%) and negative zeta potential (−41.53 ± 0.15 mV). Stability of SGE in SGE-PF68-13 was 10 times higher than the unentrapped SGE. SGE-PF68-13 showed a dose dependent activity and significantly higher therapeutic effect than the unentrapped SGE. It is concluded that encapsulation of SGE in Pluronic micelles can enhance SGE solubility, stability, and antibacterial activity. SGE-PF68-13 is suitable for further study in mammalian animals.